Calcium Phosphate Nanoparticles Functionalized with a Cardio-Specific Peptide - Federica Mancini; Lorenzo Degli Esposti; Alessio Adamiano; Jessica Modica; Daniele Catalucci; Dora Mehn; Otmar Geiss; Michele Iafisco (Nanomaterials)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide, highliting the urgent need for new therapeutic strategies. Peptide-based therapies have demonstrated significant potential for treating CVDs; however, their clinical application is hindered by their limited stability in physiological fluids. To overcome this challenge, an effective drug delivery system is essential to protect and efficiently transport peptides to their intended targets. This study introduces two distinct strategies for loading a cardio-specific mimetic peptide (MP), previously designed to modulate L-type calcium channel function in cardiomyocytes, onto calcium phosphate nanoparticles (CaP NPs). MP-loaded CaP NPs were prepared by two different wet precipitation syntheses, one of which involved the use of sodium polyacrylate as a templating agent. Characterization of MP-loaded CaP NPs showed that their crystallinity, size, surface charge, and morphology could be tuned by adjusting the synthesis parameters. In vitro tests on cardiac cells confirmed that both types of MP-loaded CaP NPs are biocompatible with HL-1 cardiomyocytes and restored intracellular calcium flux under stressed conditions, highlighting their therapeutic potential. These results pave the way for further optimization of CaP NP formulations and suggest their potential as a viable nanomaterial for CVD treatment.